Photoredox Catalysis at Copper(II) on Chitosan: Application to Photolatent CuAAC. Issue 23 (22nd October 2018) - Jennah, Oumayma; Beniazza, Redouane; Lozach, Cédric; Jardel, Damien; Molton, Florian; Duboc, Carole; Buffeteau, Thierry; El Kadib, Abdelkrim; Lastécouères, Dominique; Lahcini, Mohammed; Vincent, Jean‐Marc
Abstract: In this article we report the first example of a heterogeneous photolatent catalyst for the copper‐catalyzed azide‐alkyne cycloaddition (CuAAC) that is supported on chitosan. The heterogeneous copper(II) precatalyst was easily prepared by reaction of [Cu II 2 (3‐benzoylbenzoate)4 (H2 O)2 ] complex1 with chitosan powder. UV‐vis and EPR spectroscopy studies demonstrated that the Cu(II) ions are effectively photoreduced by low‐intensity UVAs. In particular, it was shown that the benzophenone photosensitizer, could be employed in catalytic amount, i. e. 10 mol% with respect to the Cu 2+ ions, to effectively promote the Cu(II) to Cu(I) photoreduction process. A range of triazoles, in particular those bearing sugar moieties, could be effectively synthesized under light illumination and sodium ascorbate‐free conditions. ICP analysis did not show copper contamination of the final product, thereby evidencing tight incorporation of copper on the chitosan powder. Owing to its heterogeneous nature, the catalyst could be recovered and reused several times with no appreciable decrease in the catalytic activity. As a practical application of the procedure, the anticonvulsant drug rufinamide was isolated in 82% yield on a 10 mmol scale synthesis. Abstract :